2012
DOI: 10.1073/pnas.1207367109
|View full text |Cite
|
Sign up to set email alerts
|

Y chromosome mediates ribosomal DNA silencing and modulates the chromatin state inDrosophila

Abstract: Although the Drosophila Y chromosome is degenerated, heterochromatic, and contains few genes, increasing evidence suggests that it plays an important role in regulating the expression of numerous autosomal and X-linked genes. Here we use 15 Y chromosomes originating from a single founder 550 generations ago to study the role of the Y chromosome in regulating rRNA gene transcription, position-effect variegation (PEV), and the link among rDNA copy number, global gene expression, and chromatin regulation. Based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
78
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(89 citation statements)
references
References 39 publications
8
78
0
Order By: Relevance
“…However, the origin is not strictly immediate and we cannot rule out that new mutations in it might have contributed to the difference in progeny number across grandparental backgrounds. On the other hand, sex chromosomes are sensitive to parental origin in Drosophila (Golic et al, 1998;Maggert and Golic, 2002), including substantial consequences to testis-specific gene expression and epigenetic states elsewhere in the genome (Greil and Ahmad, 2012;Zhou et al, 2012;Lemos et al, 2014). Collectively, our observations raise the prospect that genetic or epigenetic variation acquired during the making of the focal males is partially responsible for modulating hybrid male sterility.…”
Section: Discussionmentioning
confidence: 82%
“…However, the origin is not strictly immediate and we cannot rule out that new mutations in it might have contributed to the difference in progeny number across grandparental backgrounds. On the other hand, sex chromosomes are sensitive to parental origin in Drosophila (Golic et al, 1998;Maggert and Golic, 2002), including substantial consequences to testis-specific gene expression and epigenetic states elsewhere in the genome (Greil and Ahmad, 2012;Zhou et al, 2012;Lemos et al, 2014). Collectively, our observations raise the prospect that genetic or epigenetic variation acquired during the making of the focal males is partially responsible for modulating hybrid male sterility.…”
Section: Discussionmentioning
confidence: 82%
“…Studies have shown that repeat regions can play important regulatory roles (Lemos et al 2008;Zhou et al 2012) and that the proximity of coding regions to repeats (Dorer and Henikoff 1997), as well as the size of the repeating regions (Howe et al 1995;Paredes et al 2011;Sentmanat and Elgin 2012), can have unique effects on gene expression and chromatin structure. This also means that changes in repeat regions, which are notoriously difficult to detect, must also be ruled out to accurately show sequence independence.…”
Section: Dna Sequencementioning
confidence: 99%
“…In Drosophila, ChrY-mediated phenotypic differences are attributed to natural polymorphic variation in multicopy ribosomal genes present on ChrY (Lemos et al 2008(Lemos et al , 2010Paredes et al 2011;Zhou et al 2012). The musculus ChrY possesses several multicopy genes, including Sly, Rbmy, and spermiogenesis transcript on the Y 1 (Ssty1), that differ in number between ChrYs of inbred strains ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Aside from its role in male development, the Drosophila ChrY differentially regulates the expression of autosomal and ChrX genes, including a preferential enrichment of genes associated with the immune response, by altering chromatin between the heterochromatic and euchromatic state, thereby influencing numerous complex phenotypes (Lemos et al 2008(Lemos et al , 2010Piergentili 2010;Paredes et al 2011). The ability of ChrY to alter chromatin dynamics and regulate gene expression is attributed to natural polymorphic variation in the multicopy ribosomal genes present on ChrY (Paredes et al 2011;Zhou et al 2012).…”
mentioning
confidence: 99%